Elucidation of the genetic causes of bicuspid aortic valve disease. Issue 3 (21st June 2022) - Gehlen, Jan; Stundl, Anja; Debiec, Radoslaw; Fontana, Federica; Krane, Markus; Sharipova, Dinara; Nelson, Christopher P; Al-Kassou, Baravan; Giel, Ann-Sophie; Sinning, Jan-Malte; Bruenger, Christopher M H; Zelck, Carolin F; et al.
Abstract: Aims: The present study aims to characterize the genetic risk architecture of bicuspid aortic valve (BAV) disease, the most common congenital heart defect. Methods and results: We carried out a genome-wide association study (GWAS) including 2236 BAV patients and 11 604 controls. This led to the identification of a new risk locus for BAV on chromosome 3q29. The single nucleotide polymorphism rs2550262 was genome-wide significant BAV associated ( P = 3.49 × 10 −08 ) and was replicated in an independent case–control sample. The risk locus encodes a deleterious missense variant in MUC4 (p.Ala4821Ser), a gene that is involved in epithelial-to-mesenchymal transformation. Mechanistical studies in zebrafish revealed that loss of Muc4 led to a delay in cardiac valvular development suggesting that loss of MUC4 may also play a role in aortic valve malformation. The GWAS also confirmed previously reported BAV risk loci at PALMD ( P = 3.97 × 10 −16 ), GATA4 ( P = 1.61 × 10 −09 ), and TEX41 ( P = 7.68 × 10 −04 ). In addition, the genetic BAV architecture was examined beyond the single-marker level revealing that a substantial fraction of BAV heritability is polygenic and ∼20% of the observed heritability can be explained by our GWAS data. Furthermore, we used the largest human single-cell atlas for foetal gene expression and show that the transcriptome profile in endothelial cells is a major source contributing to BAV pathology. Conclusion: Our study provides a deeper understanding of the genetic risk architecture of BAV formation on the single marker and polygenic level. Graphical Abstract: Graphical Abstract